Rapid healing of cutaneous leishmaniasis by high-frequency electrocauterization and hydrogel wound care with or without DAC N-055: a randomized controlled phase IIa trial in Kabul. - Ahmad Fawad Jebran; Ulrike Schleicher; Reto Steiner; Pia Wentker; Farouq Mahfuz; Hans-Christian Stahl; Faquir Mohammad Amin; Christian Bogdan; Kurt-Wilhelm Stahl (Public Library of Science (PLoS), 2014)
Anthroponotic cutaneous leishmaniasis (CL) due to Leishmania (L.) tropica infection is a chronic, frequently disfiguring skin disease with limited therapeutic options. In endemic countries healing of ulcerative lesions is often delayed by bacterial and/or fungal infections. Here, we studied a novel therapeutic concept to prevent superinfections, accelerate wound closure, and improve the cosmetic outcome of ACL.From 2004 to 2008 we performed a two-armed, randomized, double-blinded, phase IIa trial in Kabul, Afghanistan, with patients suffering from L. tropica CL. The skin lesions were treated with bipolar high-frequency electrocauterization (EC) followed by daily moist-wound-treatment (MWT) with polyacrylate hydrogel with (group I) or without (group II) pharmaceutical sodium chlorite (DAC N-055). Patients below age 5, with facial lesions, pregnancy, or serious comorbidities were excluded. The primary, photodocumented outcome was the time needed for complete lesion epithelialization. Biopsies for parasitological and (immuno)histopathological analyses were taken prior to EC (1(st)), after wound closure (2(nd)) and after 6 months (3(rd)). The mean duration for complete wound closure was short and indifferent in group I (59 patients, 43.1 d) and II (54 patients, 42 d; p = 0.83). In patients with Leishmania-positive 2(nd) biopsies DAC N-055 caused a more rapid wound epithelialization (37.2 d vs. 58.3 d; p = 0.08). Superinfections occurred in both groups at the same rate (8.8%). Except for one patient, reulcerations (10.2% in group I, 18.5% in group II; p = 0.158) were confined to cases with persistent high parasite loads after healing. In vitro, DAC N-055 showed a leishmanicidal effect on pro- and amastigotes.Compared to previous results with intralesional antimony injections, the EC plus MWT protocol led to more rapid wound closure. The tentatively lower rate of relapses and the acceleration of wound closure in a subgroup of patients with parasite persistence warrant future studies on the activity of DAC N-055.ClinicalTrials.gov NCT00947362.